CYP2C19 pharmacogenetics in advanced cancer: compromised function independent of genotype - Helsby, N A; Lo, W-Y; Sharples, K; Riley, G; Murray, M; Spells, K; Dzhelai, M; Simpson, A; Findlay, M (British journal of cancer, 2008)
CYP2C19 is a drug-metabolising enzyme involved in the metabolism of a number of chemotherapeutic agents including cyclophosphamide. Variants of the CYP2C19 gene result in a loss of function polymorphism, which affects approximately 3% of the Caucasian population. These individuals are poor metabolisers (PM) of a wide range of medications including omeprazole (OMP). In healthy subjects PM can be identified through homozygous variant genotype. However, a discordance between CYP2C19 genotype and phenotype has been reported previously in a small study of cancer patients. To investigate whether CYP2C19 activity was decreased in patients with advanced cancer, CYP2C19 genotype was determined in 33 advanced cancer patients using PCR-RFLP analysis for the two important allelic variants ( *2 ,681G>A and *3 ,636G>A) and the activity of the enzyme was evaluated using the CYP2C19 probe drug OMP. The activity of the drug-metabolising enzyme CYP2C19 was severely compromised in advanced cancer patients, resulting in a PM status in 37% of the patients who had normal genotype. This is significantly ( P <0.0005) higher than that would be predicted from the genotypic status of these patients. There was no evidence of a correlation between compromised CYP2C19 activity and any of the proinflammatory cytokines or acute phase response proteins studied. However, there was preliminary evidence of an association between PM status and low body mass ( P =0.03). There is increasing interest in using pharmacogenetics to ‘individualise medicine’, however, the results of this study indicate that in a cancer population genotyping for CYP2C19 would significantly underestimate the number of phenotypic PM of drugs, such as cyclophosphamide, which may be metabolised by this enzyme.